Heartless sky - Peckham, Caroline; Valenti, Susanne (Peckham, Caroline. Zodiac Academy, 2025)
"The winds of fate are shifting, and it finally seems like they've been twisted in our favour. On the run and cast out from society, we've been forced to hide from the mad man who stole our throne. But as more secrets come to light and my sister and I work harder than ever before to reach our potential and claim our birth right, the end is finally drawing closer. There is no turning from this path now. The curse chases on our heels as time rushes by and the blood drenched destiny of the man I love looms ever closer just like the monster who stole our throne. We must prepare for the final battle"--Publisher description.